ANALYSIS OF NURSING CARE WITH WALKING SPORTS INTERVENTION TO REDUCE SENDENTARY BEHAVIOR IN CHILDREN WITH OBESITY IN RT 03 RW 09 GROGOL, LIMO, DEPOK - Nourmayansa Vidya Anggraini; Della Yunita (Universitas Airlangga, 2023)
Introduction: Overweight and obesity is a problem of excess nutrition that is increasingly common in children around the world. Overweight and obesity in children is the result of calorie (energy) intake that exceeds the number of calories expended or burned through metabolic processes in the body. Lifestyle changes that lead to westernization and sedentary life styles are often found in big cities in Indonesia. Simple physical activities that can overcome obesity in children include walking. Walking is a way to increase physical activity that is simple, easy, and can be done by anyone at any time. This writing aims to determine the effectiveness of walking interventions for reducing body mass index in school-age children. Method: This type of research is qualitative with a case study approach. The population in this study were obese children. Number of subjects 2. Subject criteria: obese children aged 6 to 10 years with a threshold > 2 SD based on measurements of Body Mass Index, have body characteristics: round face, double shoulders, both inner thighs are pressed against each other and rub together, distended stomach , and a relatively short neck. This research was conducted for one month. Walking exercise is done 3 times in 1 week and is done for approximately 40 minutes. Results: In resume patients, there was a weight loss of 1 kg with a decrease in BMI of 0.4 SD. So it can be concluded that the walking intervention had an effect on reducing body mass index in school-age children. Conclusion: Community nurses are expected to be able to apply walking as a management method for overcoming weight and obesity in school-age children.